Group-Theoretical Property of Slightly Degenerate Fusion Categories of Certain Frobenius-Perron Dimensions (Journal of Mathematical Study, 2023)
Let $p, q$ be odd primes, and let $d$ be an odd square-free integer such that $(pq,d)=1$. We show that slightly degenerate fusion categories of Frobenius-Perron dimensions $2p^2q^2d$, $2p^2q^3d$ and $2p^3q^3d$ are group-theoretical.
Keywords: Group-theoretical fusion category; slightly degenerate fusion category.